Unintended consequences: the EU memory framework and the politics of memory in Serbia and Croatia. Issue 3 (3rd July 2018) - Milošević, Ana; Touquet, Heleen
ABSTRACT: The shared memories of the Second World War have played a crucial role in the process of integration of the European Union (EU). After the Enlargement to the East, the EU also sought to accommodate the historical experiences of the former communist countries. The result of this process was an EU memory framework that focused on shared suffering under totalitarian (both fascist and communist) regimes. This article examines the impact of this framework and its equalization of fascism and communism on Croatia (new member state) and Serbia (in accession talks). We conclude that the framework is used locally as an opportunity structure to renegotiate ideological conflicts.